2021
DOI: 10.1111/jace.17698
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the structure, thermal, and optical properties in Al2O3‐incorporated La2O3‐TiO2‐Nb2O5 glasses

Abstract: Glasses in the 30La2O3‐40TiO2‐30Nb2O5 system are known to have excellent optical properties such as refractive indices over 2.25 and wide transmittance within the visible to mid‐infrared (MIR) region. However, titanoniobate glasses also tend to crystallize easily, significantly limiting their applications in optical glasses due to processing challenges. Therefore, the 30La2O3‐40TiO2‐(30−x) Nb2O5‐xAl2O3 (LTNA) glass system was successfully synthesized using a aerodynamic containerless technique, which improves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…α O 2− initially increased then decreased, and the overall trend is decreasing. As shown in Equation (), the refraction index is determined not only by α O 2− but also by V m , the V m for high‐entropy glass RE = La, Tm, and Lu decrease from 40.26 to 39.67, suggesting that the effect of V m is greater than α O 2− 16,25 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…α O 2− initially increased then decreased, and the overall trend is decreasing. As shown in Equation (), the refraction index is determined not only by α O 2− but also by V m , the V m for high‐entropy glass RE = La, Tm, and Lu decrease from 40.26 to 39.67, suggesting that the effect of V m is greater than α O 2− 16,25 …”
Section: Resultsmentioning
confidence: 99%
“…These are larger than those of SiO 2 (68.8 kJ/cm 3 ) and B 2 O 3 (86.0 kJ/cm 3 ) 7 . In addition, it has been reported that high field ions can induce the transformation of Al 3+ into a higher coordination number 8,13,16 . In aluminosilicate glasses, which typically range from 3% to 30% and from 1% to 2%, respectively, 17 these high‐entropy glasses reach values near 41.9% and 14.0% 8 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations